The right to the city in Latin America and the approaches to the informal city - Calderón Cockburn, Julio (2017)
The paper addresses urban issues from the concept of the right to the city. An initial location of the state of affairs from the specificity of urbanization in Latin America in their theoretical models and formal, informal or illegal processes from their own players in the Latin American city.